2019
DOI: 10.5599/jese.650
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of trace levels of Cd(II) and Pb(II) in tap water samples by anodic stripping voltammetry with 2-mercaptobenzothiazole modified electrode

Abstract: <span lang="EN-US">Glassy carbon electrode (GCE) modified by 2-mercaptobenzothiazole (MBT), mesoporous silica (Meso) and bismuth was developed to determine Cd(II) and Pb(II) simultaneously by square wave anodic stripping voltammetry (SWASV). In-situ preparation was found to work best in optimum conditions of acetate buffer pH 6, accumulation potential of <br /> -1.1 V, deposition time of 300 s and scan rate of 200 mV/s. SW peaks revealed the linear range of 5-50 µg/L Cd(II) and 5-50 µg/L Pb(II). LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In our case, we have shown that Bi/chitosan/mesoporous silica can be used in the determination of Cd (II) and Pb (II) in water lily in polluted water resources [9]. Our work might also prove that certain compounds can be used in-situ for simultaneous ASV analysis of various metals in addition to Cd (II) and Pb (II) [10]. However, the fact that Boron doped diamond (BDD) works well with Pb (II) [11] might turn out that BDD alone can be applied here for simultaneous analysis which would make it easier for onsite applications.…”
Section: Acsr000514 1(3)2019mentioning
confidence: 75%
“…In our case, we have shown that Bi/chitosan/mesoporous silica can be used in the determination of Cd (II) and Pb (II) in water lily in polluted water resources [9]. Our work might also prove that certain compounds can be used in-situ for simultaneous ASV analysis of various metals in addition to Cd (II) and Pb (II) [10]. However, the fact that Boron doped diamond (BDD) works well with Pb (II) [11] might turn out that BDD alone can be applied here for simultaneous analysis which would make it easier for onsite applications.…”
Section: Acsr000514 1(3)2019mentioning
confidence: 75%
“…Electrochemical sensors showed many advantages for the analysis of food compounds due to their fast response. High oxidation/reduction over-potential and low sensitivity of electroactive compounds at the surface of unmodified electrodes are major problems for trace level analysis [13][14][15][16][17][18][19][20]. Therefore, modified electrodes were suggested as highly powerful tools for trace-level analysis of electroactive compounds.…”
Section: Introductionmentioning
confidence: 99%